Efficacy of Cognitive Behavioral Therapy in Divorced Women for Depression, Anxiety and Loneliness symptoms: A pilot study - Nilgun ONGIDER (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: In this study, it is aimed to investigate efficacy of Cognitive Behavioral Therapy (CBT) in divorced women. For this aim, it was evaluated levels of depression, anxiety and loneliness by pre and post therapy. Method: Study sample was obtained from a special family consulting center. The sample of the study consisted of 7 divorced women. The participants was selected from women whom was divorced between 0-2 years. Among divorced women a CBT intervention program was used. This study was a pilot study about divorced women in Turkey. In this study, sociodemographic data questionnaire, Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI) and UCLA loneliness were administered. For the aim of evaluating the CBT intervention among divorced women before and after CBT sessions all the questionnaires was applied. Results: For the data analyse Wilcoxon non-parametric test was used. All the study questionnaires was compared pre and post therapy. It was found that, both depression (z= -2,64 p<0,01), anxiety (z= -2,08 p<0,05) and loneliness levels (z= -3,34 p<0,001) were significantly reduced after CBT sessions in the study sample of divorced women. Conclusion: Depression, anxiety and loneliness levels were reduced significantly after CBT sessions therefore it is interpreted that CBT was effective in divorced women. Many research in the literature highlights that divorce effected negatively on women and many common psychological problems like depression, anxiety and loneliness were been occured. So intervantion programs like CBT have been effective on the negative effects of divorce